Making the implicit explicit: A look inside the implicit discount rate - Joachim Schleich; Xavier Gassmann; Corinne Faure; Thomas Meissner (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2016)
Implicit discount rates (IDRs) are employed in energy models to capture household investment decisions, yet the factors behind the IDR and their respective implications for policy-making usually remain blurred and fractional. The proposed comprehensive framework distinguishes three broad categories of factors underlying the IDR for household adoption of energy-efficient technologies (EETs): preferences (notably over time, risk, loss, debt, and the environment), predictable (ir)rational behavior (bounded rationality, rational inattention, behavioral biases), and external barriers to energy efficiency. Existing empirical findings suggest that the factors underlying the IDRs that differ across household characteristics and technologies should be accounted for in energy models. Furthermore, the framework allows for a fresh look at the interplay of IDRs and policies. We argue that a simple observation of high IDRs (or observing correlations between IDRs and socio-economic characteristics) does not provide guid-ance for policy-making since the underlying sources cannot be identified. In-stead, we propose that some of the factors underlying the IDR - notably external barriers - can be changed (through directed policy interventions) whereas other factors - notably preferences and predictable (ir)rational behavior - are innate and can only be taken into account (through reactive policy interventions).
urn:nbn:de:0011-n-4040318
Keywords: 330; energy efficiency; energy modeling; implicit discount rate; energy policy; behavioral economics